Seminal Plasma and Seminal Plasma Exosomes of Aged Male Mice Affect Early Embryo Implantation via Immunomodulation - Wang, Dandan; Jueraitetibaike, Kadiliya; Tang, Ting; Wang, Yanbo; Jing, Jun; Xue, Tongmin; Ma, Jinzhao; Cao, Siyuan; Lin, Ying; Li, Xiaoyan; Ma, Rujun; Chen, Xi; et al. (Frontiers in Immunology, 2021)
Seminal plasma (SP), particularly seminal plasma exosomes (sExos), alter with age and can affect female mice uterine immune microenvironment. However, the relationship between fertility decline in reproductively older males and SP and sExos age-related changes, which may compromise the uterine immune microenvironment, remains unclear. The present study demonstrated that the implantation rate of female mice treated with SP from reproductively older male mice (aged-SP group) was lower than that of those treated with SP from younger male mice (young-SP group). RNA-sequence analysis revealed altered levels of dendritic cells (DCs)-related cytokines and chemokines in the uteri of the former group compared to those of the latter group. In vivo and in vitro experiments demonstrated weaker inhibitory effect of aged SP on DCs maturation than young SP upon stimulation. After isolating and characterizing sExos from young and advanced-age male mice, we discovered that insemination of a subset of the aged-SP group with sExos from young male mice partially recovered the implantation rate decline. Additional in vivo and in vitro experiments revealed that sExos extracted from age male mice exerted a similar effect on DCs maturation as SP of aged mice, indicating an age-related sExos inhibitory effect. In conclusion, our study demonstrated that age-related alterations of sExos may be partially responsible for lower implantation rates in the aged-SP group compared to those in the young-SP group which were mediated by uterine immunomodulation. These findings provide new insights for clinical seminal adjuvant therapy.